Miranda July's Intermedial Art : the Creative Class Between Self-Help and Individualism. - Czudaj, Antje (Edition Kulturwissenschaft., 2016)
This first in-depth study of Miranda July's work reveals some of its major motives and consequently provides fascinating insights into the lifestyle of the contemporary white Californian middle class. Through an analysis of July's award-winning intermedial work, the author lays open how July takes individualism and self-help as constitutive for the creative class. Although a member of the creative class herself, July's voice oscillates between irony and approval. July thus paints a fascinating portrait of neurotic hipsterism, which triggers self-reflection in the general reader and critical thinking in the cultural analyst.